Gender Differences in the Relationship Between the Nature of Intimate Partner Violence and the Survivor's Help-Seeking. (May 2020) - Cho, Hyunkag; Seon, Jisuk; Han, Jae-Bum; Shamrova, Daria; Kwon, Ilan
This study used the National Intimate Partner and Sexual Violence Survey to examine how gender interacts with the nature of intimate partner violence (IPV) in the survivor's help-seeking. A total of 3, 878 IPV survivors (869 male and 3, 009 female) were included in the study sample. Dependent variables were help-seeking and the use of formal and informal sources. Independent variables included gender, race, income, and the patterns of victimization and consequences of victimization. The results showed that survivors' characteristics and the patterns of victimization and consequences affect help-seeking, and that gender moderates the relationship between consequences and the use of formal help.